ANALISIS TINGKAT KEPUASAN PETANI PEMAKAI AIR IRIGASI COLO TIMUR DITINJAU DARI KUALITAS PELAYANAN OPERASI DAN PEMELIHARAAN SUMBER DAYA AIR BENGAWAN SOLO - Sarmin - -; Erni - Widajanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2013)
ABSTRACT The purpose of this study are: 1) Analyze the significance of the influence of tangibles to the satisfaction of farmers. 2) Analyze the significance of the influence of reliability to the satisfaction of farmers. 3) Analyze the significance of the influence responsiveness to farmers' satisfaction. 4) Analyze the significance the influence of assurance to the satisfaction of farmers. 5) Analyze the significance of the influence of empathy for the satisfaction of farmers. The population is that Farmers who gets irrigated of water Colo East have joined in the Recipient Water Farmers Association in Sukoharjo district, Karanganyar and Sragen the which amounts to 110 P3A. The sampling technique using proportional random sampling is chairman of the P3A by 55 people. Types of data using quantitative and qualitative data. Data sources using primary data and secondary data. The technique of collecting data using interviews and questionnaires. Analysis technique using a test of validity, reliability test assumptions of classical test, linear regression, test the accuracy of the model (F-test), t test, the coefficient of determination. Keywords: tangible, reliability, responsiveness, assurance and empathy farmer’s satisfaction farmers